2019
DOI: 10.1530/eje-18-0688
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in acromegaly is safe and is associated with improvements in IGF-1 concentrations

Abstract: Pregnancy is rarely reported in acromegaly. Many patients are diagnosed in later life and younger patients may have subfertility due to hypopituitarism. We present a case series of 17 pregnancies in 12 women with acromegaly. Twelve women with acromegaly who completed pregnancy were identified from centres involved in the Irish Pituitary Study. Eleven women had pituitary macroadenomas and one woman had a microadenoma. Only 5/17 pregnancies had optimal biochemical control of acromegaly preconception, as defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…In the French study, including 59 pregnancies, reported frequency of GD was 9% when IGF‐1 level was noncontrolled in preconception versus 6.4% when IGF‐1 secretion was controlled. This excess of GD is not observed in the Irish study: despite a high number of noncontrolled patients in terms of GH/IGF‐1 hypersecretion before pregnancy (12 out of 17 pregnancies, 70.6%), none developed GD . In our study, among women monitored for GD, 57% were not controlled before pregnancy (versus 29% among women without GD).…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…In the French study, including 59 pregnancies, reported frequency of GD was 9% when IGF‐1 level was noncontrolled in preconception versus 6.4% when IGF‐1 secretion was controlled. This excess of GD is not observed in the Irish study: despite a high number of noncontrolled patients in terms of GH/IGF‐1 hypersecretion before pregnancy (12 out of 17 pregnancies, 70.6%), none developed GD . In our study, among women monitored for GD, 57% were not controlled before pregnancy (versus 29% among women without GD).…”
Section: Discussioncontrasting
confidence: 67%
“…More than 150 pregnancies in women with acromegaly have been reported in the literature . So far, the prevalence of GD seems very low during pregnancies in acromegalic women, with only 5 cases of GD in 147 pregnancies .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations